Action research in education : a practical guide - Efron, Sara Efrat; Ravid, Ruth, 1939- (The Guilford Press, 2020)
"Acclaimed as a text and professional development tool, this user-friendly resource has now been revised and updated, and offers expanded coverage of collaborative action research (CAR) and participatory action research (PAR). Preservice and inservice educators get crucial step-by-step guidance for conducting classroom- and school-based studies to improve their instructional practices. Organized to mirror the full cycle of action research, the book provides balanced coverage of qualitative, quantitative, and mixed methods approaches. Vivid vignettes and examples illustrate research approaches for a range of teaching and learning situations, school subjects, and age groups (PreK-12). Readers learn how research approaches are driven by the research question, as well as how to: develop data collection strategies; design and/or evaluate assessment tools; interpret, analyze, report, and implement study results; and design a new cycle of research that builds on the previous one"--